Missing persons in the semidarkness of the afternoon: private disputes, memory and armed internal conflict in San Miguel (Ayacucho) - Cóndor Alarcón, Nory (2015)
This paper studies the case of Francisco Buendía, a man of San Miguel, in the province of La Mar (Ayacucho), who was disappeared by Sendero Luminoso in 1984. From Stathis N. Kalyvas’ theoretical offers, it reconstructs the secret microdynamics of the case, which they connected with the armed internal conflict. To find these local dynamics, one resorts to the remembrances and silences of the Buendía’s relatives and to the information that reveal the notarial and judicial documents that the memory tries to hide. This paper shows that the local dynamics contain disputes that they have to see with the process of restructuring of the land that in the locality comes from the 19th century. The disputes finally developed intopolicies, causing the disappearance of Buendía.